LiNi(0.4)Co(0.3)Mn(0.3)O(2 )thin film electrode by aerosol deposition - Kim, Icpyo (Springer, 2012)
LiNi(0.4)Co(0.3)Mn(0.3)O(2 )thin film electrodes are fabricated from LiNi(0.4)Co(0.3)Mn(0.3)O(2 )raw powder at room temperature without pretreatments using aerosol deposition that is much faster and easier than conventional methods such as vaporization, pulsed laser deposition, and sputtering. The LiNi(0.4)Co(0.3)Mn(0.3)O(2 )thin film is composed of fine grains maintaining the crystal structure of the LiNi(0.4)Co(0.3)Mn(0.3)O(2 )raw powder. In the cyclic voltammogram, the LiNi(0.4)Co(0.3)Mn(0.3)O(2 )thin film electrode shows a 3.9-V anodic peak and a 3.6-V cathodic peak. The initial discharge capacity is 44.6 μAh/cm(2), and reversible behavior is observed in charge-discharge profiles. Based on the results, the aerosol deposition method is believed to be a potential candidate for the fabrication of thin film electrodes.